2021
DOI: 10.1094/phyto-10-20-0449-r
|View full text |Cite
|
Sign up to set email alerts
|

Perception and First Defense Responses Against Pseudomonas syringae pv. phaseolicola in Phaseolus vulgaris: Identification of Wall-Associated Kinase Receptors

Abstract: Common bean (Phaseolus vulgaris L.) is attacked by several pathogens such as the biotrophic gamma-proteobacterium Pseudomonas syringae pv. phaseolicola (Pph). In order to study the Pph-bean interaction during the first stages of infection, leaf disks of a susceptible bean variety named Riñón were infected with a pathogenic Pph. Using this experimental system, six new putative Wall-Associated Kinase (WAKs) receptors, previously identified in silico, were tested. These six bean WAKs (PvWAKs) showed high protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 94 publications
0
9
0
1
Order By: Relevance
“…Plant immune-signaling pathways and transcriptional reprogramming have been proved to be activated within the first 12 hours after the apparition of the pathogen (Ngou et al, 2022). Recently, De la Rubia et al (2021a) have demonstrated that the expression of PR1 and other plant defense-related genes increased past 2 hours upon Pph infection in P. vulgaris var. riñón .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plant immune-signaling pathways and transcriptional reprogramming have been proved to be activated within the first 12 hours after the apparition of the pathogen (Ngou et al, 2022). Recently, De la Rubia et al (2021a) have demonstrated that the expression of PR1 and other plant defense-related genes increased past 2 hours upon Pph infection in P. vulgaris var. riñón .…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by the fact that P. vulgaris var. riñón is susceptible to Pph (Monteagudo et al, 2006; De la Rubia et al, 2021a) and the plant would trigger some early defense responses at 2 hours, which would be successfully stopped by the pathogen effectors at 9 hours post infection, diminishing the plant responses to Pph.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations